1994
DOI: 10.1136/bmj.309.6957.805
|View full text |Cite
|
Sign up to set email alerts
|

Kleihauer testing Need not be abandoned

Abstract: fracture radiographs by radiographers: the impact of a training programme. Br J Radiol (in press). Kleihauer testingNeed not be abandoned ED1ToR,-We recently conducted a survey of Kleihauer testing in the North Western region, and our findings are similar to those of Jennifer K M Duguid and Imelda Bromilow,' confirming the poor reproducibility and variability of the test as currently performed. We agree with Elizabeth A Letsky and Mahes de Silva that the reasons for the greater failure rate of prophylaxis with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…Recently arguments have been advanced for (Balfour et al, 1994;Love & Shwe, 1994) and against (Duguid & Bromilow, 1994) retaining the Kleihauer test. In brief, the argument against the Kleihauer test has centred around its poor reproducibility and the case for its retention on the potential for alloimmunization in women exposed to TPH not covered by a single large dose of 1250 IU anti-D. Poor reproducibility in performing the Kleihauer is not an argument for abandoning the test, but underlines the need for standardization and QA schemes to improve performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently arguments have been advanced for (Balfour et al, 1994;Love & Shwe, 1994) and against (Duguid & Bromilow, 1994) retaining the Kleihauer test. In brief, the argument against the Kleihauer test has centred around its poor reproducibility and the case for its retention on the potential for alloimmunization in women exposed to TPH not covered by a single large dose of 1250 IU anti-D. Poor reproducibility in performing the Kleihauer is not an argument for abandoning the test, but underlines the need for standardization and QA schemes to improve performance.…”
Section: Discussionmentioning
confidence: 99%
“…At present Scottish QA experience seems to support the latter view. For larger TPH, it is suggested that flow cytometry is more accurate in estimating TPHs greater than 4 mL (Love & Shwe, 1994) which occurs in about 1% of women, but relatively few district hospital blood banks will have routine access to flow cytometry. Compared with early work from the USA which showed a very poor coefficient of variation in estimation of a 'proficiency' specimen (Polesky & Serbing, 1981), our results have shown an improved CV and it is likely that the Scottish QA programme which has been in place for the last 8 years has played a role in achieving this level of reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…Recently there has been much debate regarding the measures that need to be addressed to prevent RhD iso‐immunisation 7–13 . The aim of this study was to determine the likely factors that contribute to RhD sensitisation in our region.…”
Section: Discussionmentioning
confidence: 99%
“…(1994) recommended that a more reliable test was needed to replace the 35‐year‐old Kleihauer test. However, Love & Shwe (1994) emphasized that rigorous quality assurance and standardization were the key to improving the clinical utility of this deceptively simple test.…”
Section: Discussionmentioning
confidence: 99%